2016
DOI: 10.1097/sla.0000000000001410
|View full text |Cite
|
Sign up to set email alerts
|

A Propensity-matched Analysis Comparing Survival After Esophagectomy Followed by Adjuvant Chemoradiation to Surgery Alone for Esophageal Squamous Cell Carcinoma

Abstract: Compared with surgery alone, adjuvant chemoradiation provides a survival benefit to ESCC patients, especially those with pT3/4 stage, N+ tumors, larger tumor size, poorly differentiated tumors, and R1/2 resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Previous studies have used a total dose ranging from 45 Gy to 60 Gy at 1.8 to 2 Gy per fraction. 5,19,22,[41][42][43] In the current study, 50 to 60 Gy improved OS with tolerable toxicity, which suggests that 50 to 60 Gy is reasonable. This is confirmed by reports that recommend a dose of 50 Gy or more for postoperative chemoradiotherapy in TESCC.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Previous studies have used a total dose ranging from 45 Gy to 60 Gy at 1.8 to 2 Gy per fraction. 5,19,22,[41][42][43] In the current study, 50 to 60 Gy improved OS with tolerable toxicity, which suggests that 50 to 60 Gy is reasonable. This is confirmed by reports that recommend a dose of 50 Gy or more for postoperative chemoradiotherapy in TESCC.…”
Section: Discussionmentioning
confidence: 49%
“…This is confirmed by reports that recommend a dose of 50 Gy or more for postoperative chemoradiotherapy in TESCC. 42,43 However, further studies are needed to determine the optimal PORT radiation dose in TESCC.…”
Section: Discussionmentioning
confidence: 99%
“…A few single‐centre studies have reported that postoperative chemoradiotherapy can prolong overall and recurrence‐free survival among patients with oesophageal cancer and poor prognostic factors, such as lymph node involvement and the presence of extracapsular lymph node extension. Previous studies at this centre suggested survival advantages for some patients receiving adjuvant chemoradiotherapy where pT3–4 category, lymph node involvement, larger tumour size, poor differentiation and incomplete resection might be appropriate indications for this approach. The present study aimed to analyse recurrence patterns (locoregional and distant) and survival effects from a population‐based national database of patients with oesophageal SCC who underwent curative resection with or without postoperative chemoradiotherapy, using propensity matching.…”
Section: Introductionmentioning
confidence: 98%
“…In the propensity-matched analysis by Rice and colleagues (5) (6). Our recent Taiwan Cancer Registry based study again confirmed that esophagectomy with adjuvant chemoradiation is significantly more effective than surgery alone for increasing OS (3-year OS 44.9% vs. 28.1%, P=0.006) (7). The subgroup analysis in our study even suggested that patients with pT3/4 stage, pN+ stage tumors, larger tumor size, poorly differentiated tumors, and R1/2 resections were more likely to have survival benefit from adjuvant chemoradiation.…”
mentioning
confidence: 48%